2002
DOI: 10.1136/vr.151.12.355
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and antibiotic resistance of pathogenic Escherichia coli among poultry in Belgium

Abstract: Recent advances in the epidemiology and control of parasitic gastroenteritis in sheep. Veterinary Record 92,469-473 MCKELLAR, Q. A. & MARRINER, S. E. (1987) Comparison of the anthelmintic efficacy of oxfendazole or ivermectin administered orally and ivermectin administered subcutaneously to sheep during the periparturient period. Veterinary Record 120,383-386

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…When selecting an antimicrobial drug it is important to determine the susceptibility of the bacterium isolated, as E. coli may be resistant to commonly used drugs (e.g., tetracycline, sulfonamides, ampicillin, and streptomycin). 3,4 M. gallisepticum was the second most common bacterial condition identified in birds in this retrospective disease study. Mycoplasmosis or chronic respiratory disease is an insidious respiratory disease characterized by cough, nasal and ocular discharge, and swelling of the sinuses (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…When selecting an antimicrobial drug it is important to determine the susceptibility of the bacterium isolated, as E. coli may be resistant to commonly used drugs (e.g., tetracycline, sulfonamides, ampicillin, and streptomycin). 3,4 M. gallisepticum was the second most common bacterial condition identified in birds in this retrospective disease study. Mycoplasmosis or chronic respiratory disease is an insidious respiratory disease characterized by cough, nasal and ocular discharge, and swelling of the sinuses (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Li et al [11] reported that the isolation frequency of O2 strains was 32.4% in the 1990s and 16. [8][9][10][11][12][13][14][15][16][17][18][19].6% in the 2000s in China. These data and our results showing that O2 strains have low MPC values, low mutation frequencies and difficulty in acquiring parC mutations suggest that the population of O2 strains has been decreased through the use of fluoroquinolones in the treatment of avian colibacillosis.…”
Section: Discussionmentioning
confidence: 99%
“…Enrofloxacin is an antimicrobial that is generally used to treat avian colibacillosis in Japan. Excessive use (or misuse) of fluoroquinolones can cause the emergence of bacterial strains that are resistant to this drug; thus, the emergence of fluoroquinolone resistance has been reported worldwide [2,9,18,21,22]. In Japan, approximately 20% of APEC isolates were shown to be fluoroquinolone-resistant, and serogroups O78, O8, and untypable strains resistant to fluoroquinolone have been reported [17].…”
mentioning
confidence: 99%
“…Vaccination against E. coli is limited to homologous protection, and the vaccines used against the primary agents that provoke secondary colibacillosis may themselves act as primary agents. Therapeutic treatment is expensive, often does not result in sufficient recovery before slaughter and causes increased resistance of E. coli to antibiotics (Vandemaele et al ., 2002a;Vandekerchove et al ., 2004). Breeding for reduced susceptibility to colibacillosis may contribute to its prevention, but in order to do so a meaningful breeding goal and selection criteria must be defined.…”
Section: Introductionmentioning
confidence: 99%